Dari konflik ke integrasi sosial: pelajaran dari Ambon-Maluku - Saidin Ernas, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Post-conflict in Ambon-Maluku, indicated that eventhough people were segregated in the Islamic-Christian areas, but gradually the social integration has begun to occur naturally. The process of integration that occurred also gave new values that give hope to the future of peace. Using the theory of social integration adaptation from Parsonian structural-functional Classic paradigm, this study successfully formulated several important findings. First, social integration occurred in Ambon could run naturally through economic interaction, consensus on political balances and inclusive religious spirit. Second, the new social integration has created an important meaning that leads to a model of active harmony characterized by a process of social interaction that more active between different religions. Third, this study also reminds us that although there has been a proces sof positive social integration, people still need to be aware of the growth of radical religious ideologies and also strengthening politics identity in local politics that are dangerous to the development of peace.